The Role of Electronic Accounting Information Systems in Supporting Strategic Decisions: An Exploratory Study of the Opinions of a Sample of Professionals in Private Hospitals and Academics in Sulaymaniyah Governorate - عبدالعزیز سلیمان البیاتي غازي; عثمان محمد ابوبكر (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The aim of this research is to introduce electronic accounting information systems, and to address their nature, importance and role in attributing strategic decisions in private hospitals in Sulaymaniyah Governorate. The research relied on the questionnaire form as a tool for the study, and was divided into two groups as the study sample, the first group included professionals in private hospitals; accounting managers, accountants and the administration director in Sulaymaniyah province, the second group are academics holding master’s degree and PhD in accounting, auditing, finance and management majors in Sulaymaniyah province. 8 private hospitals were selected, and 24 forms were distributed to the members of the research sample, of which 22 were returned from the total forms distributed to professionals. As for the academics, 76 forms were distributed to the sample members, of which 66 were returned out of the total forms distributed to academics. After returning the forms, it became apparent to the researcher that 5 forms are not valid for analysis, and that 83 forms are valid for analysis, and their percentage is 83% of the distributed forms. The results of the statistical analysis of the data and the survey of the opinions of the research community showed that there is a strong positive relationship and a statistically significant effect between the elements of electronic accounting information systems; input, operation and output and strategic decisions, with consideration to the inputs of electronic accounting information systems that the value of the correlation coefficient reached 0.844 and with regard to operating the accounting data, the value of the correlation coefficient reached 0.900, and with regard to the outputs of electronic accounting information systems, the value of the correlation coefficient reached 0.930, and this implies that there is a correlation between the outputs of electronic accounting information systems in support of strategic decisions.